Small ring testing of high temperature materials - Hyde, Christopher J.; Hyde, Thomas H.; Sun, Wei (Trans Tech Publications, 2017)
In service components such as steam pipes, pipe branches, gas and steam turbine blades, etc. which operate in engineering applications such as power plant, aero-engines, chemical plant etc., can operate at temperatures which are high enough for creep to occur. Often, only nominal operating conditions (i.e. pressure, temperatures, system load, etc.) are known and hence precise life predictions for these components, which may be complex in terms of geometry or weld characteristics, are not possible. Within complex components it can also be the case that the proportion of the material creep life consumed may vary from position to position within the component. It is therefore important that non-destructive techniques are available for assisting in the making of decisions on whether to repair, continue operating or replace certain components. Small specimen creep testing is a technique which can allow such analyses to be performed. Small samples of material are removed from the component to make small creep test specimens. These specimens can then be tested to give information on the remaining creep life of the component. This paper presents the results of small ring specimens tested under creep conditions and shows the comparison to standard (full size) creep testing for materials used under high temperature in industry.